Global perspectives on challenges, coping strategies, and future preparedness of nursing home staff during COVID-19: a systematic review and meta-synthesis - Xiu-fen Yang; Jia-yi Guo; Wei-si Peng; Bing-dong Wang; Chao-ran Qv; Si-jia Zhou; Rui Sun; Lulu Liao; Wei-wei Zhang; Ling-Yan Liu; Lian-chi Ren; Lin Zou; et al. (BMC Health Services Research)
Abstract Background The global public health crisis caused by COVID-19 in late 2019 was unprecedented. Due to their vulnerable population, nursing homes are a key epidemic response area. This study described the challenges and coping strategies of nursing home staff during COVID-19 and proposed recommendations for future public health crises in nursing homes. Method A meta-synthesis was performed to address the research question: What are the experiences of nursing home staff from the perspectives of COVID-19? From the beginning until August 31, 2024, searches were conducted in five international databases (CINAHL, PubMed, Web of Science, PsycINFO, and the Cochrane Library) and three Chinese databases (CNKI, VIP, and Wanfang). Two reviewers used the Joanna Briggs Institute's (JBI) qualitative research checklist to evaluate each manuscript. The findings were synthesized using pragmatic meta-aggregators. Results The meta-synthesis included 22 qualitative studies and four mixed studies, which including 906 participants was analyzed to identify 268 findings that were organized into 15 categories and combined into three syntheses. Three synthesized findings were identified: Challenges (sub-findings: challenges implementing epidemic prevention and control, resource shortage, negative emotions, inadequate departmental communication and coordination, lack of support, physical strain); coping strategies (sub-findings: role adaptation and redefinition, innovative solutions and technology, work organisation and cooperation, positive psychological service, seeking community and organisational support, Improving infection prevention awareness), and suggestions for future preparedness (sub-findings: Enhancing communication and decision-making in response to COVID-19 changes, Optimizing material supply channels and physical space, and increasing medical related team and training). Conclusion(s) This study focuses on the COVID-19 experiences and coping strategies of nursing home staff. Key coping strategies include role transition and redefinition, with staff taking on additional tasks to ensure ongoing diagnosis and treatment; innovative concepts and technologies, such as remote healthcare and digital tools, reduce the risk of infection; and strengthening collaboration and cooperation, improving efficiency, and decreasing employee workload. Mental health services and social support can alleviate stress and promote health. Maintaining optimism among staff members necessitates community and organisational support, resources, and effective communication. The findings of this study have implications for nursing home practices and policies. Sanatoriums require PPE, medical supplies, and trained personnel. Encourage system and organisational transformation. Emergency preparedness and flexible workforce initiatives enhance organisational adaptability. Increase infection prevention awareness: Sanatorium employees should get continual infection prevention training. Exploring nursing homes Layout: Relevant departments should establish criteria for the physical layout of current and prospective nursing facilities to prevent basic infectious diseases.